2009
DOI: 10.3168/jds.2008-1549
|View full text |Cite
|
Sign up to set email alerts
|

Analytical specificity and sensitivity of a real-time polymerase chain reaction assay for identification of bovine mastitis pathogens

Abstract: Intramammary infection (IMI), also known as mastitis, is the most frequently occurring and economically the most important infectious disease in dairy cattle. This study provides a validation of the analytical specificity and sensitivity of a real-time PCR-based assay that identifies 11 major pathogen species or species groups responsible for IMI, and a gene coding for staphylococcal beta-lactamase production (penicillin resistance). Altogether, 643 culture isolates originating from clinical bovine mastitis, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 18 publications
2
128
1
4
Order By: Relevance
“…Moreover, some bacteria may be present in the teat canal without causing significant inflammation, and others may be present as contaminants (Pyörälä 2003, Nunes et al 2008. Accordingly, some authors have isolated mastitis pathogens from milk samples with very low SCCs, whereas others have found high proportions of microbiologically negative milk samples with high SCCs (Makovec & Ruegg 2003, Koskinen et al 2009, Oliveira et al 2013, as found in this study. Therefore, one problem regarding the diagnosis of mastitis is that indirect tests are compared with the "golden standard" of bacteriology, although mastitis does not always require the presence of infection (Pyörälä 2003, Nunes et al 2008.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, some bacteria may be present in the teat canal without causing significant inflammation, and others may be present as contaminants (Pyörälä 2003, Nunes et al 2008. Accordingly, some authors have isolated mastitis pathogens from milk samples with very low SCCs, whereas others have found high proportions of microbiologically negative milk samples with high SCCs (Makovec & Ruegg 2003, Koskinen et al 2009, Oliveira et al 2013, as found in this study. Therefore, one problem regarding the diagnosis of mastitis is that indirect tests are compared with the "golden standard" of bacteriology, although mastitis does not always require the presence of infection (Pyörälä 2003, Nunes et al 2008.…”
Section: Discussionsupporting
confidence: 55%
“…Similar ranges were obtained when PCR-based molecular methods were compared with culture (Paradis et al, 2012;Spittel and Hoedemaker, 2012). However, molecular methods have been shown to higher detection potential than culture (Koskinen et al, 2009;Koskinen et al, 2010). We also show that the rapid detection of barely cultivatable and slow-growing mastitis pathogens, such as M. bovis, by PCR/ESI-MS represents a major advantage for veterinarians in preventing the spread of the disease within respective herds (Aebi et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Although PCR-based platforms for the detection of mastitis pathogens directly in milk have been evaluated, 17,21 an extensive study of the ability of PCR assays to distinguish between Acholeplasma and Mycoplasma species using fieldbased milk samples has not been made. The results reported herein are consistent with previous findings that identified 2 PCR products for Acholeplasma species and 1 PCR product for all Mycoplasma species as described.…”
Section: Discussionmentioning
confidence: 99%